Loss of Oca2 disrupts the unfolded protein response and increases resistance to endoplasmic reticulum stress in melanocytes. (9th September 2013) - Cheng, Tsing; Orlow, Seth J.; Manga, Prashiela
Summary: Accumulation of proteins in the endoplasmic reticulum (ER) typically induces stress and initiates the unfolded protein response (UPR) to facilitate recovery. If homeostasis is not restored, apoptosis is induced. However, adaptation to chronic UPR activation can increase resistance to subsequent acute ER stress. We therefore investigated adaptive mechanisms in Oculocutaneous albinism type 2 ( Oca2 )‐null melanocytes where UPR signaling is arrested despite continued tyrosinase accumulation leading to resistance to the chemical ER stressor thapsigargin. Although thapsigargin triggers UPR activation, instead of Perk‐mediated phosphorylation of eIF2α, in Oca2 ‐null melanocytes, eIF2α was rapidly dephosphorylated upon treatment. Dephosphorylation was mediated by the Gadd34‐PP1α phosphatase complex. Gadd34‐complex inhibition blocked eIF2α dephosphorylation and significantly increased Oca2 ‐null melanocyte sensitivity to thapsigargin. Thus, Oca2 ‐null melanocytes adapt to acute ER stress by disruption of pro‐apoptotic Perk signaling, which promotes cell survival. This is the first study to demonstrate rapid eIF2α dephosphorylation as an adaptive mechanism to ER stress.